"To have healthy leisure is to have balance": Young adults' conceptualization of healthy and unhealthy leisure. (27th May 2019) - Weybright, Elizabeth H.; Son, Julie S.; Caldwell, Linda L.
Abstract: Leisure is an important developmental context in adolescence and emerging adulthood due to its role promoting healthy development and mitigating risk behavior. Empirical work has focused on the benefits and risks of activities and time use in these life stages, but the influence of subjective perceptions of leisure is often ignored. Furthermore, researchers lack consistent conceptualization of the terms healthy leisure and unhealthy leisure . Given this, the current study used a two-phased qualitative design collecting free-listing ( nsubjects = 158) and focus group ( nsubjects = 29; ngroups = 4) data on the perceived meanings of healthy leisure and unhealthy leisure in college students. Guided by free-listing results, focus group data were analyzed for commonalities. Descriptors of healthy were restorative, self-determined, and including a social element while unhealthy was excessive, lacked self-control, and included elements of escape. Findings illustrate the challenge of labeling leisure activity as healthy or unhealthy independent of contextual and individual factors and inform measurement development.